2017
DOI: 10.1002/brb3.769
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying absolute glutamate concentrations in nucleus accumbens of prescription opioid addicts by using 1H MRS

Abstract: Introduction The diagnosis of psychoactive substance use disorders has been based primarily on descriptive, symptomatic checklist criteria. In opioid addiction, there are no objective biological indicators specific enough to guide diagnosis, monitor disease status, and evaluate efficacy of therapeutic interventions. Proton magnetic resonance spectroscopy ( 1 H MRS) of the brain has potential to identify and quantify biomarkers for the diagnosis of opioid dependence. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Benzodiazepines and non-benzodiazepine sedative-hypnotics can change body temperature in animal models [31,32] and brain glutamine synthesis [33], but effects on brain temperature, NAA, CHO, or MI have not been reported [34]. Opioids similarly have been shown to affect brain glutamate in reward system areas [35][36][37][38], but not NAA, CHO, or MI. Two human studies have found reduced NAA in frontal gray matter in opioid addicted individuals [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines and non-benzodiazepine sedative-hypnotics can change body temperature in animal models [31,32] and brain glutamine synthesis [33], but effects on brain temperature, NAA, CHO, or MI have not been reported [34]. Opioids similarly have been shown to affect brain glutamate in reward system areas [35][36][37][38], but not NAA, CHO, or MI. Two human studies have found reduced NAA in frontal gray matter in opioid addicted individuals [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In sum, our study is the first which involved that high quality glutamate spectrum can reliability be obtained from a ~3.4 cm 3 nucleus accumbens voxel using a 70-cm wide-bore clinical 3T MRI system with the short-echo-time PRESS. Studies using 1 H-MRS have reported differences in glutamatergic neurotransmitter concentrations in nucleus accumbens between healthy and clinical populations such as alcohol-dependent or opioid-dependent (Bauer et al, 2013 ; Liu et al, 2017 ). Reliable quantification of glutamate using 1 H-MRS with a wide-bore clinical 3T MRI system would be beneficial for clinical studies relating to glutamate in the human nucleus accumbens.…”
Section: Discussionmentioning
confidence: 99%
“…Although dopamine strongly contributes to the reinforcing properties of all drugs of abuse including opioids [reviewed in (31)], a robust literature implicates dysregulated homeostasis at glutamatergic synapses in OUD-associated cognitive impairments and cue reactivity (i.e., craving) (32,33). For example, glutamate levels measured by magnetic resonance spectroscopy in reward-associated brain regions in opioid-dependent users correlate positively with measures of impulsivity (34), and opioid-conditioned cues evoke craving in parallel with functional magnetic resonance imaging measures of increased activity in corticostriatal and amygdalostriatal glutamatergic circuits (35). In this review, we explore the preclinical data that identify the cellular underpinnings of these OUD-induced glutamatergic adaptations found in human imaging studies.…”
Section: Preclinical Models Of Opioid Addictionmentioning
confidence: 99%